ICT-Based Teaching Materials on Science Learning to Improve 21st-Century Skills : A Systematic Review - Naffa Afkarina Izzata Dini; Muhammad Ikhsan; Oky Pamungkas; Heru Kuswanto (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This research aims to evaluate how integrating ICT teaching materials in science learning enhances students' active involvement and develops critical 21st-century skills necessary for their daily lives and future careers. Method: A Systematic Literature Review (SLR) method is used in this study to review recent research on ICT teaching materials to improve skills for the 21st century. The results obtained were 23 articles. Results: The analysis shows that 1) E-modules are the most widely used teaching material, 2) Improving 21st-century skills, namely critical thinking. Thus, e-modules are an ideal solution to support the development of critical thinking skills in the modern era. Novelty: The novelty of this study lies in its emphasis on e-modules as a particularly effective tool for nurturing critical thinking skills among students. This focus represents a significant advancement in the educational field by demonstrating how e-modules can serve as a targeted and strategic approach to cultivating essential 21st-century skills. Using modern technology in learning, e-modules make learning more exciting and help students think critically. This is important for succeeding in today's world, which is becoming more complex and relies on technology.